Quid pro quo in online medical consultation? Investigating the effects of small monetary gifts from patients. Issue 4 (2nd February 2022) - Zhao, Wei; Liu, Qianqian Ben; Guo, Xitong; Wu, Tianshi; Kumar, Subodha
Abstract: Recent years have seen robust growth in online medical consultation platforms. These platforms allow patients to access various healthcare services provided by doctors (e.g., health assessment, diagnosis, consultation, and supervision). In China, many such platforms allow patients to give small monetary gifts to doctors as an expression of gratitude. The implicit assumption is that expensive gifts influence doctors' medical service and generate conflicts of interest but small gifts do not. However, there is little empirical evidence to support this assumption. In order to fill this gap in the literature, our study investigates whether small gifts from patients impact the quality of service provided to the gift‐givers (i.e., direct effect) and the nongivers (i.e., spillover effect). We examine three aspects of online medical service quality: (i) patient wait time, (ii) the amount of information in doctors' responses, and (iii) the degree of emotional support in doctors' responses. We find that despite the gifts' negligible monetary value, doctors who receive gifts do reciprocate to the gift‐givers by providing them with more timely responses and greater emotional support. Furthermore, after receiving the small gifts, doctors may be slower in responding to nongivers and offer them less emotional support. We also investigate whether these effects (both direct and spillover effects) vary with doctors' backgrounds, including their professional experience and geographic location. Our findings have both theoretical and practical implications for patients, online medical consultation platforms, and healthcare policy makers.